Analisis Perkembangan Teori Viktimologi dan Implikasinya Terhadap Anak Sebagai Korban Tindak Pidana Kekerasan Dalam Rumah Tangga - Andrian Eka Darma Saputra; Ayu Romadina; Muhammad Hasan Makki (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
The importance of victimology in the protection of children who are victims of domestic violence in Indonesia, because in this case there are many cases but legal protection has not maximized its application. This research uses a descriptive qualitative approach and collects data from literature, including journals, books, and other sources relevant to child victims of domestic violence. Children need legal protection as victims of domestic violence. However, in the Indonesian legal system, the protection of victims has not received sufficient attention. The rights of victims are often ignored, while the rights of criminal suspects or defendants are more strictly regulated in law. This can make victims of domestic violence feel that they are not getting justice. The role of victimology in the struggle for human rights and responsibilities is significant in the context of this issue. The study of the evolution of victimology from its origins to the present is the subject of this research, with an emphasis on the protection of children as victims of domestic violence. The author aims to understand more deeply this issue and to identify the consequences of the theory of victimology in ensuring the protection of children who have been victimized. Through the analysis of this research, a deeper understanding of the importance of legal protection for child victims of domestic violence will be obtained. The ultimate goal is to raise awareness and implement measures that protect children in the Indonesian criminal justice system. Keywords: Child, Domestic Violence, Victim, Legal Protection, Victimology